(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Fabrication and evaluation of the Isoniazid loaded sodium alginate nanoparticles (NPs) was main objective of current investigation. These NPs were engineered using ionotropic gelation technique. The NPs fabricated, were evaluated for average particle size, encapsulation efficiency, drug loading, and FTIR spectroscopy along with in vitro drug release. The particle size, drug loading and encapsulation efficiency of fabricated nanoparticles were ranging from 230.7 to 532.1 nm, 5.88% to 11.37% and 30.29% to 59.70% respectively. Amongst all batches studied formulation F-8 showed the best sustained release of drug at the end of 24 hours.